Intermédialité et vulgarisation des savoirs historiques à l’ère de la post-radiophonie : le cas de « Au cœur de l’histoire » (Europe 1) - Séverine Equoy Hutin (Amnis)
This study looks into the dynamics of passage from one media – radio – to another – the Web – and specifically how historical knowledge is staged within the framework of a semio-pragmatic approach to mass-media communication. How does one produce « history for all » in the age of webradio? Taking as a case study the program « Au coeur de l'Histoire » (« At the heart of History ») presented by Franck Ferrand and broadcast on the French radio station Europe 1, we show that the context of intermediality creates a specific access to knowledge and appropriation which changes the initial radio experience. Observing the frames for writing, and the ways that knowledge aimed at the « general public » and at co-enunciator « users » and based on this broadcast and on the direct and indirect ramifications which are proposed on the Web, allows us to look into these structures as places for encounters and interaction between knowledge and the web/radio user public.